Case Report: Omalizumab-associated hair loss: a case of eyebrow alopecia areata, literature review and FAERS database analysis - Wang, Qian; Lei, Hua; Yang, Ge; Li, Ying; Liu, Wei; Zhang, Lixia; Zhou, Xiyuan (Frontiers in Medicine, 2025)
Hair loss is a rare adverse reaction associated with omalizumab, with limited literature reports. The incidence, underlying mechanisms, and clinical characteristics of omalizumab-associated hair loss have not been clarified. We report a 52-year-old female with chronic spontaneous urticaria (CSU) who developed significant loss of eyebrows after 12 weeks of omalizumab treatment at 300 mg per 4 weeks. The diagnosis of alopecia areata (AA) was confirmed through dermoscopic examination and clinical manifestation. While maintaining omalizumab treatment for CSU, topical 0.03% tacrolimus ointment was initiated for treatment of AA. Regrowth of eyebrows was observed at 28 weeks of omalizumab treatment. We then performed a literature review, analyzing eight patients from five articles and one conference abstract, and concurrently analyzed data from 756 cases reported in the FDA adverse event reporting system (FAERS) database of patients developing alopecia after omalizumab use. Our findings suggest that omalizumab may induce alopecia, particularly among females and individuals aged 18–60 years. However, establishing a direct cause-effect relationship between alopecia and the drug remains challenging. AA may be the more uncommon type of omalizumab-associated hair loss, though it may be a transient phenomenon. Even if the incidence of this adverse effect is low, it warrants the clinician’s attention. Improved recognition of omalizumab-associated hair loss can optimize pretreatment preparation and patient counseling.